El Amicus Curiae en las decisiones del Tribunal Constitucional Plurinacional - Castagne Arce, Kinish (Universidad Andina Simón Bolívar, Sede Central Sucre, 2022)
El autor en esta investigación trata de precisar cuál la importancia del instituto del amicus curiae en la historia y posterior jurisprudencia Boliviana, para luego identificar el procedimiento que ha venido otorgando el Tribunal Constitucional Plurinacional de Bolivia sobre el instituto del amicus curiae, para que después del análisis del derecho comparado a través del estudio de la legislación o jurisprudencia nacional con (México, Argentina, Ecuador, Estados Unidos de Norteamérica, Corte Interamericana de Derechos Humanos), finalmente termine proponiendo un procedimiento sobre la aplicación de la figura del amicus curiae que facilite la participación de la sociedad en las sentencias del Tribunal Constitucional Plurinacional de Bolivia.

The author in this research tries to specify the importance of the institute of amicus curiae in the history and subsequent Bolivian jurisprudence, to then identify the procedure that has been granted by the Plurinational Constitutional Tribunal of Bolivia on the institute of amicus curiae, so that after the analysis of comparative law through the study of legislation or national jurisprudence with (Mexico, Argentina, Ecuador, United States of America, Inter-American Court of Human Rights), finally ends up proposing a procedure on the application of the figure of amicus curiae that facilitates the participation of society in the judgments of the Bolivian Constitutional Court, Argentina, Ecuador, United States of America, Inter-American Court of Human Rights), it finally ends up proposing a procedure on the application of the figure of the amicus curiae that facilitates the participation of society in the judgments of the Plurinational Constitutional Tribunal of Bolivia.
The Amicus Curiae in the decisions of the Plurinational Constitutional Tribunal
1. Introducción -- 2. Marco teórico -- 3. Diagnóstico -- 4. Propuesta -- 5. Bibliografía
Keywords: Amicus Curiae; Derecho Constitucional; Participación ciudadana en procesos judiciales